2016
DOI: 10.1155/2016/9039754
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PGC-1αPrevents the Beneficial Effect of EET-Heme Oxygenase-1 on Mitochondrial Integrity and Associated Metabolic Function in Obese Mice

Abstract: Background/Objectives. Obesity and metabolic syndrome and associated adiposity are a systemic condition characterized by increased mitochondrial dysfunction, inflammation, and inhibition of antioxidant genes, HO-1, and EETs levels. We postulate that EETs attenuate adiposity by stimulating mitochondrial function and induction of HO-1 via activation of PGC-1α in adipose and hepatic tissue. Methods. Cultured murine adipocytes and mice fed a high fat (HF) diet were used to assess the functional relationship among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Concomitantly inhibition of HO activity reduces mitochondrial quality control by inhibition of mitochondrial fusion mediator Mfn1, Mfn2 and Opa1 but activation of mitochondrial fission mediator Fis1 [42], [43]. Hence, our study offers a portal on the unique role of HO-1 in adipose tissue by its ability to maintain mitochondrial quality and biogenesis.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Concomitantly inhibition of HO activity reduces mitochondrial quality control by inhibition of mitochondrial fusion mediator Mfn1, Mfn2 and Opa1 but activation of mitochondrial fission mediator Fis1 [42], [43]. Hence, our study offers a portal on the unique role of HO-1 in adipose tissue by its ability to maintain mitochondrial quality and biogenesis.…”
Section: Discussionmentioning
confidence: 71%
“…Specific TaqMan ® Gene Expression Assays probes for mouse HO-1, PGC1α, COX-IV (cytochrome c oxidase subunit-IV), adiponectin, TNFα, and other signaling RNA were determined as previously described [42], [43].…”
Section: Rna/real-time Polymerase Chain Reaction (Pcr) Of Thermogenicmentioning
confidence: 99%
“…Adipo-ORF-HO-1 lentivirus and adipo-Sh-HO-1 clone were cultured. A similar procedure was used to isolate TWIST silencing, as previously described [10,35,36].…”
Section: Generation Of Lentiviral Vector-mediated Ho-1 Overexpressed mentioning
confidence: 99%
“…Obesity is associated with inflammation of the heart, often leading to myocardial infarction, reduction in left ventricular function, and reduced ejection fraction [5,6]. White fat, whether epicardial or visceral, is considered a major source of inflammation [7][8][9] and leads to a reduction in mitochondrial thermogenesis and biogenesis signaling [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, endothelium‐specific CYP2J2 overexpression alleviates high‐fat diet‐induced hyperlipidemia via increased fatty acid oxidation mediated by the AMPK pathway (Zhang et al., ). It has also been reported that EET‐A (an EET analogue) increased mitochondrial biogenesis and insulin sensitivity, thereby providing metabolic syndrome protection in high‐fat diet‐induced obesity in mice (Singh, Bellner et al., ; Singh, Schragenheim et al., ). These studies reinforce the importance of the development of EETs as promising drugs for the treatment of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%